The role of online hemodiafiltration with endogenous reinfusion in the treatment of systemic lupus erythematosus activity resistant to conventional therapy - Elghiriani, Mohammed A.; Naga, Salah S.; Hameed, Ibtessam A.; Elgohary, Iman E.; Mansour, Amal R. (Frontiers in Nephrology, 2024)
IntroductionLupus is a diverse autoimmune disease with autoantibody formation. Lupus nephritis carries a grave prognosis. Complement involvement, namely, C1q deficiency, is linked to activity and renal involvement and could help in their assessment. LN therapies include plasma exchange, immune adsorption, and probably hemodiafiltration with online endogenous reinfusion (HFR), together with traditional immunosuppressive therapies.AimThe aim of this study was to evaluate the role of HFR in improving signs and symptoms of systemic lupus erythematosus (SLE) activity and laboratory parameters in cases not responding to traditional immunosuppressive therapy.Settings and designA controlled clinical study was conducted on 60 patients with lupus from Group A that was subdivided into two groups: cases 1 (47 patients), those who received traditional medical treatment, and cases 2 (13 patients), those who underwent HFR in addition to medical treatment. Group B consisted of two subgroups: control 1, composed of 20 healthy age- and sex-matched volunteers, and control 2, consisting of 10 cases with different glomerular diseases other than lupus.Methods and materialsSerum C1q was determined before and after the HFR as well as induction by medical treatment. Disease activity was assessed using SLEDAI-2K with a responder index of 50; quality of life was assessed using SLEQOL v2, and HFR was performed for the non-responder group.ResultsC1q was lower in cases. It can efficiently differentiate between SLE patients and healthy controls with a sensitivity of 81.67% and a specificity of 90%. It can also efficiently differentiate between SLE patients and the control 2 group (non-lupus patients with renal glomerular disease) with a sensitivity of 83.33% and a specificity of 100%. C1q was more consumed in proliferative lupus, and correlated with anti-ds DNA, C3, and C4.ConclusionsC1q efficiently discriminates lupus patients and correlates with proliferative forms. HFR might ameliorate lupus activity and restore C1q.